Diseño probabilístico de estructuras de madera en Norteamérica - Dávalos Sotelo, Raymundo (Instituto de Ecología, A.C., 2016)
The subject of reliability-based design for North America is reviewed. The objective of probabilistic design using First order Second moment methods is described. These Methods are based on the concept of safety index, from which the probability of failure, Pf, can be estimated. Calibration procedures for the design equations are discussed. Load factors specified by different codes for usual loading combinations are presented, as well as the resistance-reducing factors. One argument in favor of probabilistic design is that it provides a quantitative measurement of the safety of structures. However, quite often, the differences between observed and predicted failure rates are substantial. Some of the reasons for these discrepancies are presented. Results from the literature indicate that the serviceability requirement of the current codes could be insufficient in terms of reliably predicting the functional behavior of modern structures.